Securing Job by the Educated Tribal Youths of Tripura: Issues and Challenges: Exploring the Employment Challenges Faced by Educated Tribal Youths in Tripura (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Government or the Pvt. Job is very needful to an educated man‟s life for surviving a morallife. An educated young person is searching his better job to earn money for the development himself andfor his family welfare. He tries to fulfil his desires and for his family needs. It can change a person‟s lifestyle. It brings the confidence self-respect and social status which makes them feel the part of society.But for securing the better job of an educated Tribal candidate is the challenging issue in this presentera. The government of India and the states have been given the good opportunity of reservationespecially for the Tribal and others community but could not fill up vacant in higher level posts. Thegovernment facilitates more and more through the welfare departments sponsoring the educationalcoaching centres for the different and better job or employment of Tribal community but not beensuccess. There are a lot of reasons to fail of achieving the jobs for the Tribal youths of Tripura.The mainfactor of failing job securing among the tribal youth of Tripura is socialization. Department of central andstate governments, Companies of government and private, Institutions and NGOs are the main platformand scope of formal job but thousands of Tripura Tribal Youth being unemployed.